Show, Not Tell: The Contingency Role of Infographics Versus Text in the Differential Effects of Message Strategies on Optimistic Bias. Issue 6 (December 2019) - Huang, Guanxiong; Li, Kang; Li, Hairong
Using an online between-subject experiment, this study tested the effects of message framing (gain vs. loss), reference point (self vs. other), and modality (text vs. infographics) in the scenario of recycling promotion. The findings identified that modality determines under what circumstances message strategies make a difference in risk perception and optimistic bias. In particular, only when paired with infographics and other-referencing point are loss-framed messages more effective than gain-framed messages in increasing risk perception and reducing the self-other gap in perceived benefits. Moreover, risk perception variables and the self-other risk perceptual gap were significant predictors of promoted behavioral intentions.